2018
DOI: 10.1039/c8sm00863a
|View full text |Cite
|
Sign up to set email alerts
|

Modelling DNA extension and fragmentation in contractive microfluidic devices: a Brownian dynamics and computational fluid dynamics approach

Abstract: We simulated the thorough process of DNA fragmentation in microfluidics. The conformation of DNA preconditioned by shear flow and the strain rate of elongational flow are two critical parameters for DNA fragmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…In laminar flows, considerable progress has been made in the modelling and simulation of polymer scission (e.g. Cascales & de la Torre 1991, 1992Hsieh, Park & Larson 2005;Sim, Khomami & Sureshkumar 2007;Wu et al 2018). However, the knowledge gained from the study of laminar flows cannot be directly applied to turbulent flows because of the different properties of the strain rate, and consequently of the flow-induced polymer stretching, in the two types of flows.…”
Section: Introductionmentioning
confidence: 99%
“…In laminar flows, considerable progress has been made in the modelling and simulation of polymer scission (e.g. Cascales & de la Torre 1991, 1992Hsieh, Park & Larson 2005;Sim, Khomami & Sureshkumar 2007;Wu et al 2018). However, the knowledge gained from the study of laminar flows cannot be directly applied to turbulent flows because of the different properties of the strain rate, and consequently of the flow-induced polymer stretching, in the two types of flows.…”
Section: Introductionmentioning
confidence: 99%
“…Figure a shows that the fan-shaped flat liquid jets near nozzles broke up into small droplets, which is similar to the previous studies. The size of the liquid sheet increased as the KGM concentration increased, indicating that adding KGM inhibited the breakup of liquid jets. The length of a liquid jet is shown in Figure b, and the average liquid jet length increased from 3.21 to 6.22 cm as the KGM concentration increased from 0 to 0.25% (Figure c,d).…”
Section: Resultsmentioning
confidence: 99%
“…The simulation method was reported in previous studies ,, (Supporting Information, Sections S11–S13). Briefly, the multi-scale simulation method combining computational fluid dynamics (CFD) and Brownian dynamics simulation (BD) was used to simulate the dynamic behavior of a single KGM molecule in flow fields.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was shown that pDNA was more susceptible to shear-induced degradation in low ionic strength solvents, such as ultrapure pDNA lysates, or mixed solvents with a fractional water content . Despite these important insights, the rotating shear disk device used to generate shear in those experiments did not accurately reproduce the numerous interfaces and spatially dependent shear fields encountered in an increasing number of pDNA formulations. …”
Section: Introductionmentioning
confidence: 99%